Widely conserved miRNAs in buffalo milk extracellular vesicles survive gastrointestinal digestion and potentially target neural and immunomodulatory contexts - Ilori, Olubukunmi Amos; Santoro, Jessie; Abrego-Guandique, Diana Marisol; Tucci, Paola; Smaldone, Giovanni; Cione, Erika (Frontiers in Nutrition, 2025)
MicroRNAs (miRNAs) are small non-coding RNAs with unique functions. Their presence in human milk raises the possibility of accumulation along the food chain. Buffalo milk extracellular vesicles, as other milks, are a known source of dietary miRNAs. However, information on the digestive stability of miRNAs remains limited, which is a prerequisite for understanding their in vivo functionalities. To this, the presence of widely conserved miRNAs: miR-10a-5p, miR-24-3p, miR-25-3p, miR-26a-5p, miR-27b-5p, miR-33a-5p, miR-103a-3p, miR-125b-5p, miR-130a-3p, miR-133a-3p, miR-138-5p, miR-139-5p, miR-141-3p, miR-148a-3p, miR-153-3p, miR-199a-3p and miR-223-3p, were assessed in isolated extracellular vesicles, extracted from buffalo milk. The miR-10a-5p, miR-24-3p, and miR-130a-3p, were not detected in raw buffalo milk. Therefore, we simulated the gastrointestinal digestion using INFOGEST 2.0 and extracted extracellular vesicles from the digest. Apart from particle numerosity, which differed significantly, from 1.2 × 1011 ± 5.3 × 109 particles/mL in raw milk to 9.53 × 1010 ± 1.2 × 109 particles/mL in digested milk, the extracted extracellular vesicles showed no structural differences before and after digestion. The miRNA cargo exhibited a similar pattern, except miR-141-3p, miR-153-3p, both increased slightly, and miR-223-3p, which increased substantially; miR-148a-3p, which decreased; and miR-33a-3p, which was no longer detectable after digestion. The bioinformatics analysis of the overall 13 miRNAs detected post-digestion, concertedly target neural and immunological contexts, with an MHC-mediated antigen processing and presentation. The prospect offered highlights the potential of milk, through its EV-miRNA fraction, to impact inflammatory responses in the neurodevelopmental processes of the benefiting offspring, and by extension, dairy consumers. However, relevant in vitro and in vivo investigations are needed to demonstrate the post-digestion transfer of these nucleic acids from the concerned dietary sources and their effect on target tissues.